CYBER CRIMES AGAINST WOMEN IN INDIA - Ahlawat, Himani; Sharma, Somlata (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The fast growth of technology and extensive internet usage have resulted in an alarming increase in cybercrime, particularly targeting women. In India, where women already face enough obstacles in the physical world, the internet domain has become yet another source of harassment and abuse. This study investigates the many types of cybercrimes committed against women in India, their socio-legal ramifications, and legislative and judicial reactions to these crimes. It also investigates the effects of such crimes on women’s mental health, freedom of expression, and overall involvement in the digital economy. This study uses case studies and statistical analysis to expose weaknesses in existing regulations and propose remedies to tackle this growing threat.